2019
DOI: 10.1016/j.physa.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of linear mixing in EEG on synchronization and complex network measures studied using the Kuramoto model

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Therefore, the information on EEG signals is obtained just by analyzing the characteristics of the graph. In our previous works, we showed that the synchronization measure based on the HVG algorithm is a robust measure for finding correlation among chaotic, noisy and stochastic signals [37], and also this measure is less sensitive to the brain volume conduction effect and is able to predict the coupling degree correctly even with strongly overlapping signals [38]. This synchronization measure is presented here shortly.…”
Section: Functional Network Analysismentioning
confidence: 81%
“…Therefore, the information on EEG signals is obtained just by analyzing the characteristics of the graph. In our previous works, we showed that the synchronization measure based on the HVG algorithm is a robust measure for finding correlation among chaotic, noisy and stochastic signals [37], and also this measure is less sensitive to the brain volume conduction effect and is able to predict the coupling degree correctly even with strongly overlapping signals [38]. This synchronization measure is presented here shortly.…”
Section: Functional Network Analysismentioning
confidence: 81%
“…In order to simulate the neuronal current propagation from the source regions within the brain to the EEG electrodes, several electrical models have been proposed: from simple n-sphere models (in which each concentric spherical region represents different brain layers) to more accurate models based on information from other neuroimaging techniques [18]. To simulate the source activity, also different procedures have been used, such as dipole generators, potential meshes, and oscillators [10,18,19]. The most extended electrical model in EEG source analysis is the boundary element method (BEM) [20].…”
Section: Introductionmentioning
confidence: 99%
“…skin, skull, cerebrospinal fluid (CSF), gray and white matter) are inside the head [22,23]. However, these methods do not allow the characterization of the influence of volume conduction in coupling estimators, since the simulation of ideal scenarios without volume conduction is not feasible [10,19]. A first approach to evaluate the influence of EEG volume conduction in different connectivity metrics was performed by Stam et al [10], and another recent study replicated this one with the same limitations [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We seek to take a step toward integrating the key strengths of both of these approaches by proposing a communication-inspired variation of the Kuramoto-Sakaguchi (K-S) model. The K-S model is a wellstudied coupled oscillator model incorporating phase delays [9,20], and has been used to capture BOLD [7,10,[21][22][23], MEG [24], and EEG [25,26] dynamics. Individual oscillators are set at an intrinsic frequency of 40-60 Hz, which can be understood to replicate lo-cally synchronous neural firing in the gamma range.…”
Section: Introductionmentioning
confidence: 99%